Themes in the Album We All Fall A Sleep, Where Do We Go? by Billie Eillish - Irmawati Noer Shaumi (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
This study entitled Themes in the Album We All Fall A Sleep, Where Do We Go? By Billie Eillish. The research method used is a qualitative descriptive method using data collection techniques, read, observe and note. Then, for data analysis, several stages are conducted, namely data condensation, data presentation and drawing conclusions. The data source used are taken from the album We All Fall A Sleep Where Do We Go? By Billie Eillish. This study aims to describe the themes contained in the album and describes the message contained in it. Based on this research, it was found that from the album it produces three themes, namely fear, loss and hatred; and then there are three messages, namely the biggest fear is yourself, respect someone before leaving and don't do things that are detrimental to yourself. Keywords: Theme, Message, Fear, Loss, Hatred